Pelatihan Guiding untuk Pemuda ASIDEWI & Pokdarwis di Desa Wisata Kampung Patin Koto Masjid Kampar - Syaifullah; Herlinawati; Syahdan (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2023)
Kampung Patin or Koto Masjid Kampar village offers a wide variety of tourism products, such as culinary, nature and souvenirs. The last three years this village has been visited by many tourists from neighboring provinces, such as West Sumatra, North Sumatra and Jambi. In 2021, this village was awarded the ADWI (Indonesian Tourism Village Award) by the minister of Tourism. In addition, in the same year it also won the second National Champion award as a tourism village in the field of souvenirs. The results of the initial survey of researchers through the chairman of ASIDEWI (Association of Tourism Villages) Koto Masjid, after a lengthy discussion related to the progress of the village, especially in tourism, collaboration with related parties is urgently needed, especially to improve the quality of tourism actors there. Furthermore, the chairman of ASIDEWI said that; "So far there has been no training or learning for youth/Pokdarwis in Patin village as one of the tourism actors in the village about Guiding, we hope there will be an academic group willing to share knowledge about it," he said. Based on the results of the initial survey in the village of Koto Masjid above, the service team has sponsored training activities on Guiding for youth as tourism actors in the village of Koto Masjid or Kampung Patin. As a result, the participants felt very helpful and increased their knowledge about guiding and their hopes that there needs to be continuity and variation from this activity in the future.